![\left\{{{2x+}\frac{x-y}{4}=11\atop{3y-\frac{x-y}{3} =1}}\right.\\\\\\\left\{{{2x+}\frac{x-y}{4}=11|*4\atop{3y-\frac{x-y}{3} =1|*3}}\right.\\ \\\\\left\{{{8x+(x-y)=44}\atop{9y-(x-y)=3}}\right.\\ \\\left\{{{9x-y=44}\atop{10y-x=3|*9}}\right.\\\\\left\{{{9x-y=44}\atop{-9x+90y=27}}\right. \left\{{{2x+}\frac{x-y}{4}=11\atop{3y-\frac{x-y}{3} =1}}\right.\\\\\\\left\{{{2x+}\frac{x-y}{4}=11|*4\atop{3y-\frac{x-y}{3} =1|*3}}\right.\\ \\\\\left\{{{8x+(x-y)=44}\atop{9y-(x-y)=3}}\right.\\ \\\left\{{{9x-y=44}\atop{10y-x=3|*9}}\right.\\\\\left\{{{9x-y=44}\atop{-9x+90y=27}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7B2x%2B%7D%5Cfrac%7Bx-y%7D%7B4%7D%3D11%5Catop%7B3y-%5Cfrac%7Bx-y%7D%7B3%7D%20%3D1%7D%7D%5Cright.%5C%5C%5C%5C%5C%5C%5Cleft%5C%7B%7B%7B2x%2B%7D%5Cfrac%7Bx-y%7D%7B4%7D%3D11%7C%2A4%5Catop%7B3y-%5Cfrac%7Bx-y%7D%7B3%7D%20%3D1%7C%2A3%7D%7D%5Cright.%5C%5C%20%5C%5C%5C%5C%5Cleft%5C%7B%7B%7B8x%2B%28x-y%29%3D44%7D%5Catop%7B9y-%28x-y%29%3D3%7D%7D%5Cright.%5C%5C%20%5C%5C%5Cleft%5C%7B%7B%7B9x-y%3D44%7D%5Catop%7B10y-x%3D3%7C%2A9%7D%7D%5Cright.%5C%5C%5C%5C%5Cleft%5C%7B%7B%7B9x-y%3D44%7D%5Catop%7B-9x%2B90y%3D27%7D%7D%5Cright.)
Сложим эти уравнения:
\\\\10*\frac{71}{89}-x=3\\\\x=\frac{710}{89}-3=\frac{710-89*3}{89}=\frac{443}{89}=4\frac{87}{89}\\\\x=4\frac{87}{89};y=\frac{71}{89}" alt="9x-y-9x+90y=44+27\\\\89y=71\\\\y=\frac{71}{89}\\ \\10y-x=3=>\\\\10*\frac{71}{89}-x=3\\\\x=\frac{710}{89}-3=\frac{710-89*3}{89}=\frac{443}{89}=4\frac{87}{89}\\\\x=4\frac{87}{89};y=\frac{71}{89}" align="absmiddle" class="latex-formula">